INSTITUTE FOR PRIVATE BAILIFF - Коzhakhmetova, Раушан Жайыковна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2022)
The article is devoted to the institution of private law-enforcement officers in the Republic of Kazakhstan, to the practice and problems of application of certain provisions of the Law of the Republic of Kazakhstan "About Executory Process and the Status of Law-enforcement Officers " in the activities of law-enforcement officers.